Implementing standardized performance indicators to improve hypertension control at both the population and healthcare organization levels - Campbell, Norm (J Clin Hypertens (Greenwich), 2017)
The ability to reliably evaluate the impact of interventions and changes in hypertension prevalence and control is critical if the burden of hypertension‐related disease is to be reduced. Previously, a World Hypertension League Expert Committee made recommendations to standardize the reporting of population blood pressure surveys. We have added to those recommendations and also provide modified recommendations from a Pan American Health Organization expert meeting for “performance indicators” to be used to evaluate clinical practices. Core indicators for population surveys are recommended to include: (1) mean systolic blood pressure and (2) mean diastolic blood pressure, and the prevalences of: (3) hypertension, (4) awareness of hypertension, (5) drug‐treated hypertension, and (6) drug‐treated and controlled hypertension. Core indicators for clinical registries are recommended to include: (1) the prevalence of diagnosed hypertension and (2) the ratio of diagnosed hypertension to that expected by population surveys, and the prevalences of: (3) controlled hypertension, (4) lack of blood pressure measurement within a year in people diagnosed with hypertension, and (5) missed visits by people with hypertension. Definitions and additional indicators are provided. Widespread adoption of standardized population and clinical hypertension performance indicators could represent a major step forward in the effort to control hypertension.